Construction and Analysis of the Dysregulated ceRNA Network and Identification of Risk Long Noncoding RNAs in Breast Cancer - Su, Xiaojie; Yu, Zhaoyan; Zhang, Yuexin; Chen, Jiaxin; Wei, Ling; Sun, Liang (Frontiers in Genetics, 2021)
Breast cancer (BRCA) is the second leading cause of cancer-related mortality in women worldwide. However, the molecular mechanisms involved in the development of BRCA is not fully understood. In this study, we constructed a specific long non-coding RNAs (lncRNAs) - protein coding gene (PCGs) competitive endogenous RNA (ceRNA) network for BRCA by merging the global ceRNA network and specific dysregulated lncRNAs and PCGs co-expression network in BRCA. Then, we performed the random walking with restart (RWR) method to prioritize BRCA related lncRNAs through comparing their RWR score and significance. As a result, we identified 30 risk lncRNAs for BRCA, which can distinguish normal and tumor samples. Moreover, through gene ontology and KEGG pathway analysis, we found that these risk lncRNAs mainly synergistically perform functions related to cell cycle and DNA separation and replication. At last, we developed a four-lncRNAs prognostic signature and assessed the survival accuracy of the signature by performing time-dependent receiver operating characteristic (ROC) analysis. The area under the ROC curve for 1, 3, 5 and 10 years of survival prediction were 0.68, 0.61, 0.62 and 0.63, respectively. The multivariable Cox regression results verified that the four-lncRNAs signature can predict BRCA patients’ survival independently. In summary, these results have important reference value for the study of diagnosis, treatment and prognosis evaluation of BRCA.